La escisión del héroe como un viaje interior de (auto)conocimiento: Aprehensión del mundo y del “yo” por la fragmentación, en Miguel de Cervantes, Italo Calvino y Zigmunds Skujiņš - Gatti Riccardi, Giuseppe (Verbum – Analecta Neolatina, 2019)
In our essay the Bajtinian notion of dialogism is applied to the intertextual dialogue that is established between some themes of Cervantes’s Don Quixote and two “producers of discourses” of the 20th century: the Italian Italo Calvino (1903–1985) and the Latvian Zigmunds Skujiņš (1926). We will try to demonstrate how a literary motif of fantastic features – the survival of a human being divided into two halves by the effect of a violent action – offers the three writers the possibility of describing a journey of (self) knowledge. In Don Quixote all the adventures of Alonso Quijano have been part of a learning process necessary for Alonso to understand his condition and heal his madness before saying goodbye to the world. In Il visconte dimezzato Calvino establishes a explicitly declared dialogue with Cervantes: he outlines for his “unfolded protagonist” and his grandson (the narrator) a journey of self-understanding that focuses on the problem of contemporary man, alienated and incapable to be fully realized. Finally, in the novel Como piezas de un domino, through the motive of the disintegration of the human being Skujiņš reflects on the national identity and draws for his characters a journey through history, dominated by the themes of disintegration and duplicity of identity.